Mestizo modernity : race, technology, and the body in postrevolutionary Mexico - Dalton, David S. (Reframing Media, Technology, and Culture in Latin/o America., 2018)
This book discusses the work of José Vasconcelos, Diego Rivera, José Clemente Orozco, Emilio "El Indio" Fernández, El Santo, and Carlos Olvera. These artists--and many others--held diametrically opposed worldviews and used very different media while producing works during different decades. Nevertheless, each of these artists posited the fusion of the body with technology as key to forming an "authentic," Mexican identity.